Fresno County Young Lawyers Association Halloween Dance at Crossland's Barn - Watkins, Howard::::::::: (1984)
Legal Tender Band: Dave Maybary on saxophone, Nano Talanoa back on drums, John B. Smith guitar, Ken Fransen, Tom Riche and Lorraine Bolen singers, Bob Fishman guitar